2018
DOI: 10.1159/000484275
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid: The Unknown Uremic Toxin

Abstract: This review brings together concepts of uric acid metabolism affecting renal parenchyma and its function and the current therapies to reduce hyperuricemia (HyU) and avoid renal disease progression. High uric acid plays an important role in several chronic diseases including kidney diseases such as lithiasis, gout nephropathy, and preeclampsia. In the last 30 years, it has been shown that reducing HyU with low protein and low purine diets in addition to allopurinol creates physiopathological conditions that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…The association between uric acid levels and damage accrual in patients with SLE was evaluated, and serum uric acid level was found to be associated with the development of new damage in these patients. Previous studies have found an association between hyperuricaemia and hypertension,13 metabolic syndrome14 and renal disease,2 as well as with organ failure or damage,15 especially renal 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between uric acid levels and damage accrual in patients with SLE was evaluated, and serum uric acid level was found to be associated with the development of new damage in these patients. Previous studies have found an association between hyperuricaemia and hypertension,13 metabolic syndrome14 and renal disease,2 as well as with organ failure or damage,15 especially renal 16…”
Section: Discussionmentioning
confidence: 99%
“…The solubility of uric acid at normal physiological pH is generally given at 6.8 mg/dL, with reference ranges for uric acid of 3.5–7.2 mg/dL (210–430 µmol/L) and 2.6–6.0 mg/dL (155–360 µmol/L) in younger men and premenopausal women, respectively 1. Hyperuricaemia is the result of increased production or decreased excretion of uric acid 2. Uric acid levels have been associated with increased risk of heart mortality,3 increased risk of kidney disease4 and as a predictor of metabolic syndrome 5…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricemia has been found to independently predict the development of diabetes and mediate insulin resistance in both fructose-dependent and fructose-independent models of metabolic syndrome. 33 Abnormal total cholesterol level is a risk factor for occurrence of sight-threatening DR and diabetic macular edema, and higher serum triglyceride level is a risk factor for PDR in subjects with type 2 diabetes. Dyslipidemia with abnormal levels of total cholesterol, LDL, HDL, and triglyceride is associated with greater risk of incident diabetic macular edema and greater risk for progression to PDR, compared with abnormal levels of individual lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have been carried out to investigate the effects of ULT on CKD progression (reviewed in [42,57,58]). While many trials have reported that ULT has a benefit on renal outcomes, others found that ULT provided no benefit [59].…”
Section: Role Of Urate-lowering Therapy In Prevention Of Ckdmentioning
confidence: 99%